2020
DOI: 10.5964/ejop.v16i1.1934
|View full text |Cite
|
Sign up to set email alerts
|

Humor styles and empathy in junior-school children

Abstract: Humor is a complex phenomenon. For one individual a joke may be perceived as comical, yet for another, the same joke may be deemed completely inappropriate. The appropriate use of humor is perhaps dependent on how a humorist relates to, understands and can empathize with their audience. Thus, the present research aimed to determine whether empathy is related to junior-school children’s use of different humor styles. It has been proposed that four styles of humor exist, two of which are thought to be adaptive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…For example, some children use humour to cope with stress, while others use it as a way to show aggression (Führ, 2002). Others, such as Halfpenny and James (2020), stated that Martin's adaptive and maladaptive humour styles can be used to explain children's cognitive empathy, affective empathy and sympathy. Moreover, Erikson and Feldstein (2007) sought to investigate the relation between the psychometric properties of children and different humour behaviours using Martin's humour styles.…”
Section: Martin's Humour Styles Theorymentioning
confidence: 99%
“…For example, some children use humour to cope with stress, while others use it as a way to show aggression (Führ, 2002). Others, such as Halfpenny and James (2020), stated that Martin's adaptive and maladaptive humour styles can be used to explain children's cognitive empathy, affective empathy and sympathy. Moreover, Erikson and Feldstein (2007) sought to investigate the relation between the psychometric properties of children and different humour behaviours using Martin's humour styles.…”
Section: Martin's Humour Styles Theorymentioning
confidence: 99%
“…By 10-11 years, children begin to understand hyperbole and exaggerated irony in humor (Aguert et al 2018;Varga, 2000). Affiliative, rather than aggressive style of humor is seen in 9-11 year junior school children (Halfpenny & James, 2020) within classrooms. The number of laughter events in children with higher social status was significantly higher than in those with lower status (Hatano et al 2016).…”
Section: School Childrenmentioning
confidence: 99%
“…For the relationship between affective empathy and aggression, a common-sense and intuitive view holds that after observing the pain displayed by the victim, the attacker will automatically and vicariously experience the pain, which will make the attacker unwilling to continue hurting the victim and thus reduce aggressive behaviors (Miller & Eisenberg, 1988). A growing body of studies have found affective empathy to negatively relate to different forms of aggression (e.g., verbal aggression, physical aggression, and aggressive humor; Dryburgh & Vachon, 2019; Halfpenny & James, 2020; Kokkinos & Voulgaridou, 2019). Therefore, improving affective empathy ability has become one of the core goals of therapy programs for violence and aggressive behaviors (Vachon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%